Immunological platelet transfusion refractoriness: current insights from mechanisms to therapeutics - Xiaoyu Chen; Yuhong Zhao; Yan Lv; Jue Xie (Platelets)
Although there have been tremendous improvements in the production and storage of platelets, platelet transfusion refractoriness (PTR) remains a serious clinical issue that may lead to various severe adverse events. The burden of supplying platelets is worsened by rising market demand and limited donor pools of compatible platelets. Antibodies against platelet antigens are known to activate platelets through FcγR-dependent or complement-activated channels, thereby rapidly eliminating foreign platelets. Recently, other mechanisms of platelet clearance have been reported. The current treatment strategy for PTR is to select appropriate and compatible platelets; however, this necessitates a sizable donor pool and technical assistance for costly testing. Consolidation of these mechanisms should be of critical significance in providing insight to establish novel therapeutics to target immunological platelet refractoriness. Therefore, the purposes of this review were to explore the modulation of the immune system over the activation and elimination of allogeneic platelets and to summarize the development of alternative approaches for treating and avoiding alloimmunization to human leukocyte antigen or human platelet antigen in PTR.